Earthquake vulnerability assessment of households along the West Valley Fault zone and its implications in building resilient community the case of Makati eastside cluster - Walde, Anthony Xenon L.; Liwag, Carmelita R.E.U.; Delos Reyes, Mario R.; Castro, Jun T. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
Natural disaster events are frequently occurring and causing heavy damages not only to lives and properties. One study conducted in 2004 still the basis for the major earthquake preparation for Metro manila; this is the Metro Manila Earthquake Impact Reduction Study (MMEIRS). The Study focused on Model 08, as the worst-case scenario, this is when a 7.2 Magnitude earthquake occurred along the west valley fault. The Study projected based from the given scenario that 170,000 residential houses will collapsed, 340,000 residential houses will be partly damaged, 34,00 persons will die, 114,000 persons will be injured. Fire will breakout and burnt approximately 1,710 hectares and totally 18,000 additional persons will be killed by this secondary disaster. Moreover, infrastructures and lifelines will also be heavily damaged.A segment of West Valley Fault (WVF) traverses the eastern part of Makati City, which affects six barangays namely: West Rembo, East Rembo, Comembo, Pembo, Rizal and Post Proper Southside. Based from the Contingency Plan of Makati for Earthquake, when the worst scenario occurred during daytime, there would be an estimated 4.2 million people in the City, deaths at 2,300 deaths (0.5 percent of the total population) and 84,822 injured (1.6 percent). there will be displacement of 1,260,000 persons (30 percent of daytime population), there will be 9,092 structures that are heavily damaged, 16,694 partially damaged, and 4,983 burned down. Since the study investigated the earthquake vulnerability, there are 323 lots and 311 structures located in an area of 58,381.96sq. meters using the 10-meter buffer zone. Only 155 households were investigated after preliminary assessing the data gathered. This study attempted to assess the level of vulnerability of the households living within the buffer zone of the West Valley Fault of the Eastside Cluster in Makati. Only East Rembo, Comembo, Pembo, Rizal are considered in the Study since they formed part of the Eastside Cluster. The Study developed a tool to evaluate the level of vulnerability for Makati City in relation to four contributing factors namely: geologic, structural, economic and social. The tool treats the four factors that are calculated based from the general framework of risk employed by UNDP Risk = hazard x exposure x vulnerability. Appropriate fractile classifications under an assumed beta probability distribution, which is generally skewed and takes values within the interval (0, 1) were applied to measure the level of vulnerability for each factors and to the overall vulnerability level.Based on the calculation and analyses done., Geologic Vulnerability is consistently high in all four barangays compared with the three other factors and it greatly influenced the assessed level of the overall vulnerability. For Structural Vulnerability, the roofing materials caused the vulnerability to be low, for economic it is evident that risk transfer and financial support mechanism explains the vulnerability condition of the Study Area, while for social-programs and projects through increased budgetary allocation to disaster risk reduction and management activities, earthquake awareness and the presence of vulnerable segments such as children and senior citizens. Integrating the factors to generate the Overall Vulnerability Index, most of the households or 59 percent are level High while 40 percent ae in the moderate or medium level of vulnerability. In terms of the number of households in the high level considering the location, there are 45 households from Rizal and 33 households from East Rembo, making the two barangays as a primary area for possible interventions to reduce vulnerability and increase resiliency. Investigating at the household level, among the top 20 most vulnerability households, 16 are located in Rizal while two from Pembo, one from Comembo and one from East Rembo. Although the top 5 most vulnerability households are all located in barangay Rizal.The Study was enabled to pinpoint specific houses with the level of vulnerability based on four factors. Recommendations, measures and interventions were also forwarded by the Study to reduce vulnerabilities of the community and the households based from the elements presented by the Study.
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Emergency management -- Philippines -- Makati City; Earthquakes -- Philippines -- Makati City; Earthquake hazard analysis -- Philippines -- Makati City; Earthquake intensity -- Philippines -- Makati City; Fault zone -- Philippines -- Makati City